Trend analysis of new hepatitis C cases in Brazil: 2011 to 2019 - Kassada, Danielle Satie; Nogueira, Isabela Cristina; Camargo, Amanda Dal Checo; Castro, Gabriel Borba de; Rocha, Igor de Lima Peixoto; Rueda, Aline Gonçalez; Oliveira, Henrique Ceretta (O Mundo da Saúde, 2024)
Hepatitis C virus (HCV) infection is a disease transmitted through exposure to the blood or other body fluids of infected people as a result of unsafe health practices and care, unscreened blood transfusions, injecting drug use, and sexual practices without the use of condoms. This study aims to analyse the trend in new cases of hepatitis C in Brazil from 2011 to 2019. Data were collected from HCV cases registered in the Notifiable Diseases Information System in all regions of Brazil from 2011 to 2019. The information collected included the following variables: sex, colour/race, region of notification, transmission mechanism and age group. A trend analysis was then performed using the Joinpoint programme with a 5% significance level. In Brazil, 154,978 new cases of hepatitis C were reported. Regarding the trend of new hepatitis C cases in Brazil between 2011 and 2019, a decreasing trend was observed between 2016 and 2019. The data analysed in the study showed that new cases of hepatitis C in Brazil are on a downward trend, especially among men, whites, children under one year of age, people aged 20-59 years, and in the southern and central-western regions of the country. Despite being a notifiable disease, several variables remain blank, highlighting the low quality of information collection. Brazil faces significant barriers to eradicating the disease by 2030. Overcoming these barriers will require investment in infrastructure and comprehensive public policies, as well as an integrated approach that regional the various variables involved.